Complementary Law 123/2006: passive joinder of public entities in lawsuits involving the Supersimples Law (Revista do Tribunal Regional Federal da 3ª Região, 2012)
The Federal Constitution provides for differentiated treatment for micro and small businesses, including unified tax collection. Complementary Law 123/2006, regulating this treatment, created passive procedural substitution, giving the Union legitimacy to defend the interests of the other federal entities. I will address concepts related to tax jurisdiction, procedural substitution, standing and res judicata, in order to demonstrate that the Union's exclusive standing in lawsuits involving the Supersimples is open to question, including its constitutionality.
Keywords: national simple law; exclusive passive rights; micro companies